The role of monetary policy in the formation of fixed capital in the industrial sector and its impact on gross domestic product in Iraq during the period (1990- 2017) - Ali, Monem Hussain; Farhan, Mohsen Owaid (Journal of Economic, Administrative and Legal Sciences, 2020)
The research aims to activate the role of some variables of monetary policy in influencing the gross domestic product in Iraq, through its impact on the total fixed capital formation of the industrial sector, as the study includes two models: the first is the effect of monetary variables on the total fixed capital formation of the industrial sector, and the second Measuring the extent of the impact of the total fixed capital formation of the industrial sector on the gross domestic product, as the results of the standard analysis showed that monetary policy variables have a significant effect on the gross domestic product indirectly through their impact on the total fixed capital formation of the domestic sector Industrial, through the value of (R2 = 0.98 and R2 = 0.97 respectively) in the two models, which means that (98% and 97%) of the changes in the dependent variable are due to the independent variables included in the two models, respectively, as well as the value of (F = 85.00360) And (F=207.7157) for the two models, respectively, at the level of significance of 5% and the probability value (Prob 0.000) to the presence of a common integration between the variables included in the two models, which means a long- term balance relationship, as indicated by the value of (DW = 2.668733) and (DW = 2.345350) for the two models. Respectively, there is no problem of self - correlation of the values ​​of the random variable, and this means that monetary policy affects the gross domestic product of Through the use of cash channels to influence the productive sectors in the industrial sector, which in turn affects the total fixed capital formation of the industrial sector that leads to an increase in the level of economic activity in Iraq.
Keywords: money supply; interest rate; exchange rate; gross fixed capital formation; gross domestic product